2010
DOI: 10.1002/humu.21355
|View full text |Cite
|
Sign up to set email alerts
|

Musculocontractural Ehlers-Danlos Syndrome (former EDS type VIB) and adducted thumb clubfoot syndrome (ATCS) represent a single clinical entity caused by mutations in the dermatan-4-sulfotransferase 1 encoding CHST14 gene

Abstract: To cite this version:Fransiska Malfait, Delfien Syx, Philip Vlummens, Sofie Symoens, Sheela Nampoothiri, et al.. Musculocontractural Ehlers-Danlos syndrome (former EDS type VIB) and adducted thumb clubfoot syndrome (ATCS) represent a single clinical entity caused by mutations in the dermatan-4-sulfotransferase 1 encoding CHST14 gene.. Human Mutation, Wiley, 2010, 31 (11) show that both conditions form a phenotypic continuum. Our findings confirm that the EDSvariant associated with CHST14 mutations (Miyake, et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
123
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(132 citation statements)
references
References 30 publications
2
123
0
Order By: Relevance
“…EDS VIB had also been used to describe a different disorder now known as brittle cornea syndrome (MIM# 229200). Malfait et al [2010] reported additional patients with CHST14 mutations and confirmed the overlap of ATCS and some of the EDS VIb patients. The name for the phenotype characterized by CHST14 mutations is ''EhlersDanlos syndrome, musculocontractural type.''…”
Section: Nosologymentioning
confidence: 65%
“…EDS VIB had also been used to describe a different disorder now known as brittle cornea syndrome (MIM# 229200). Malfait et al [2010] reported additional patients with CHST14 mutations and confirmed the overlap of ATCS and some of the EDS VIb patients. The name for the phenotype characterized by CHST14 mutations is ''EhlersDanlos syndrome, musculocontractural type.''…”
Section: Nosologymentioning
confidence: 65%
“…It is 95% for EDS type IV (COL3A1 gene), 6 EDS types VIIA and VIIB (COL1A1 and COL1A gene, respectively) and EDS type VIA (PLOD1 gene). 7 Sensitivity is not known in the recessively inherited clinical entities including Brittle Cornea syndrome 1 and 2 (ZNF469 and PRDM5 gene), 11 D4ST1-deficient EDS (CHST14 gene), 8 FKBP14-deficient EDS, 12 dermatosparactic type (ADAMTS2 gene), 9 EDS progeroid form (B4GALT7 gene) and EDS spondylocheiro dysplastic form (SLC39A13 gene). 10 …”
Section: Clinical Sensitivity (Proportion Of Positive Tests If the DImentioning
confidence: 99%
“…Homozygous or compound heterozygous CHST14 mutations have been found in 11 patients aged 0 day to 6 years at the initial publication (from four families) with ATCS [Dündar et al, 1997[Dündar et al, , 2001[Dündar et al, , 2009Janecke et al, 2001;Sonoda and Kouno, 2000], in six patients aged 2-32 years (from six families) with EDSKT [Kosho et al, 2005Miyake et al, 2010;Yasui et al, 2003], and in three patients aged 12-22 years (from two families) with MCEDS [Malfait et al, 2010]. Lack of detailed clinical information from later childhood to adulthood in ATCS and lack of detailed clinical information from birth to early childhood in EDSKT and MCEDS have made it difficult to determine whether the three conditions would be distinct clinical entities or a single clinical entity with variable expressions and with different presentations depending on the patients' ages at diagnosis , though the latter notion was suspected to be appropriate [Janecke et al, 2011;Malfait et al, 2010].…”
mentioning
confidence: 99%
“…Lack of detailed clinical information from later childhood to adulthood in ATCS and lack of detailed clinical information from birth to early childhood in EDSKT and MCEDS have made it difficult to determine whether the three conditions would be distinct clinical entities or a single clinical entity with variable expressions and with different presentations depending on the patients' ages at diagnosis , though the latter notion was suspected to be appropriate [Janecke et al, 2011;Malfait et al, 2010]. We, therefore, have just published an article in American Journal of Medical Genetics Part A, describing detailed clinical findings and courses of two additional unrelated EDSKT patients, aged 2 and 6 years, which could definitely unite the three conditions [Shimizu et al, 2011].…”
mentioning
confidence: 99%
See 1 more Smart Citation